Património, Saúde e Medicina, ou a Arte de dar Vida à Memória. Trilhos de Cultura & Ciência - Nunes, Maria de Fátima (Trabalhos de Antropologia e Etnologia, 2020)
Campo de Sant’Ana shares memory: political, scientific, and urban. The liberalism of 1817-1820 established the Field of Fatherland’s Martyrs [Campo Mártires da Pátria]. The year 1906 stamped the scientific internationalization, welcoming the XV International Congress of Medicine. The 1930s is shaped by the Goethe Institute. This hill offers several layers of temporal memory, heritage, collections, artifacts, buildings that combine to produce knowledge with citizenship practices. Doing “the archeology of ideas and words” in the “Hill of Health” allows opening to the social sciences this cultural and scientific space of Lisbon, capital of several “historical-geographical complex”.